Prescriptive appropriateness in early breast cancer staging exams: preliminary investigation about adherence to the guidelines in the clinical practice - Errico, Angelo; Di Rito, Alessia; Sallustio, Alessandra; Bardoscia, Lilia; Bambace, Santa; Portaluri, Maurizio; Guglielmi, Giuseppe; Tramacere, Francesco (Acta Biomedica Atenei Parmensis, 2023)
.